INOVASI PELAYANAN PERMOHONAN SALINAN PUTUSAN ONLINE (PERSALINAN) (STUDI KASUS KANTOR PENGADILAN NEGERI SURABYA) - Atika Milasari; Trenda Aktiva Oktariyanda (Publika, 2022)
Pelayanan PERSALINAN merupakan inovasi di Pengadilan Negeri Surabaya untuk meningkatkan pelayanan dalam putusan perkara online. Lamanya proses pengambilan putusan di pengadilan, serta banyaknya pengaduan yang masuk terkait dengan pengurusan salinan putusan, menjadi salah satu faktor diciptakannya inovasi pelayanan PERSALINAN. Oleh sebab itu, penelitian ini bertujuan untuk mendeskripsikan pelayanan PERSALINAN berdasarkan faktor keberhasilan inovasi. Jenis penelitian yang digunakan yaitu deskriptif kualitatif dengan teknik pengumpulan data, terdiri atas: wawancara, studi literatur, serta dokumentasi. Faktor keberhasilan inovasi menggunakan enam indikator yang dikemukakan oleh Arundel, Bloch, & Ferguson (2019), diantaranya: governance and innovation; sources of ideas for innovation; innovation culture; capabilities, and tools; objective, outcomes, drivers, and obstacles; collecting innovation data for single innovations. Hasil penelitian didapatkan bahwa indikator governance and innovation bahwa sistem regulasi atau kebijakan yang digunakan telah sesuai dengan prosedur yang telah ditetapkan. Sources of ideas for innovation diperoleh dari internal dan eksternal. Innovation culture didukung oleh pimpinan, kemampuan adaptasi pegawai administrasi layanan putusan perkara, serta mudahnya prosedur pelayanan bagi pengguna. Capabilities and tools yaitu asistensi dari petugas IT terhadap petugas pengelola administrasi putusan dan penggunaan website dan fitur pendukungnya. Objective, outcomes, drivers, and obstacles, yaitu: memberikan kepastian dan kemudahan pengguna layanan; hasilnya telah mendapatkan tingkat kepuasan 70%; faktor pendorong berupa regulasi, e-goverment, dan faktor penjaminan pelayanan mutu; sedangkan hambatannya yaitu berupa sarana dan prasarana, anggaran, serta rendahnya kompetensi SDM. Collecting innovation data for single innovations tidak melibatkan pihak eksternal selain pengguna layanan, serta tidak terintegrasi dengan stakeholder, inovasi ini telah melakukan beberapa pembaharuan fitur website maupun program pelayanan. Kata Kunci : Pelayanan Publik, Inovasi Pelayanan, PERSALINAN The PERSALINAN service is an innovation at the Surabaya District Court to improve services in online case decisions. The length of the decision-making process in court, and the number of incoming complaints related to the processing of copies of the decision, are factors for the creation of innovation in childbirth services. Therefore, this research aimed to describe the PERSALINAN service based on the success factors of innovation. The type of research used is descriptive qualitative with data collection techniques, consisting of: interviews, literature studies, and documentation. The innovation success factor uses six indicators proposed by Arundel, Bloch, & Ferguson (2019), including: governance and innovation; sources of ideas for innovation; innovation culture; capabilities and tools; objectives, outcomes, drivers, and obstacles; collecting innovation data for single innovations. The results showed that the indicators of governance and innovation are that the regulatory system or policy used is following the established procedures. Sources of ideas for innovation are obtained from internal and external sources. The innovation culture is supported by the leadership, the adaptability of administrative staff for case decision services, and the ease of service procedures for users. Capabilities and tools, namely assistance from IT officers towards decision administration management officers and the use of the website and its supporting features. Objectives, outcomes, drivers, and obstacles, namely: providing certainty and convenience for service users; the results have obtained a satisfaction level of 70%; driving factors in the form of regulation, e-government, and quality service assurance factors; while the obstacles are in the form of facilities and infrastructure, budget, and the low competence of human resources. Collecting innovation data for single innovations does not involve external parties other than service users and is not integrated with stakeholders; this innovation has carried out several website feature updates and service programs. Keywords: Public Service, Innovation Service, PERSALINAN